Pimobendan oral solution is bioequivalent to pimobendan chewable tablets in beagle dogs - Olaf Kuhlmann; Michael Markert (Journal of Veterinary Internal Medicine)
Abstract Background Myxomatous mitral valve disease (MMVD) is frequently diagnosed in small breed dogs. Pimobendan oral solution has been developed to improve dosing accuracy in small and toy breed dogs. Hypothesis/Objectives Demonstrate bioequivalence of pimobendan oral solution with pimobendan chewable tablets using a pharmacokinetic and a pharmacodynamic study in healthy purpose bred dogs. Animals In the pharmacokinetic study, 24 beagle dogs were dosed in a 4‐period crossover design. In the pharmacodynamic study, 4 mongrel and 2 beagle dogs implanted with telemetry probes were included in a 2‐way crossover design. Methods Both studies were designed as prospective, randomized crossover trials. Dogs were given single doses of 5 mg/dog of either formulation followed by serial blood sampling for determination of pimobendan and O‐desmethyl‐pimobendan (ODMP; main metabolite). Because of high variability in the pharmacokinetics, the reference scaled average bioequivalence (RSABE) method was applied. For the pharmacodynamic study, animals were dosed with 0.25 mg/kg of either formulation. Baseline corrected left ventricular maximal pressure (LVdP/dtmax) and heart rate were recorded continuously and compared with a predefined bioequivalence threshold. Results Pimobendan was verified as a high variability drug. Based on the RSABE method, both formulations were bioequivalent. Pharmacodynamic results supported bioequivalence. Conclusions and Clinical Importance The novel oral solution of pimobendan was found to be bioequivalent, both applying the Food and Drug Administration (FDA) supported RSABE method and based on pharmacodynamic data. Thus, the novel liquid formulation can be used to facilitate accurate dosing of small and toy breed dogs.